Comparison of two methods of dental prophylaxis: evaluation of arterial pressure and patient comfort in a clinical randomized controlled trial - Ferreira, Camila Lopes; Santos, Lucio Murilo Dos; Melo Filho, Antonio Braulino De; Santamaria, Mauro Pedrine; Jardini, Maria Aparecida Neves (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
AbstractIntroduction The number of hypertensive patients is increasing and prophylaxis with bicarbonate jet are widely performed in clinical practice using large amounts of this substance in a short period of time, which may lead to increased arterial pressure. In the literature there are several studies that analyze the effect of sodium bicarbonate jet on the biofilm and dental structures, but not report the effect on arterial pressure.Aim Evaluated the change in arterial pressure before and after two procedures of dental prophylaxis, jet baking soda application and conventional prophylaxis, and patient opinion of the comfort of each system was obtained.Material and method We selected 20 patients aged 18 to 30 in need of prophylaxis to remove biofilm. The patients were placed into three different treatment groups: sodium bicarbonate jet (G1), conventional prophylaxis (G2) and control (G3), with a one month interval between treatments. Patients were divided into groups randomly. Measurements were performed immediately before and after the procedure, 15 and 30 minutes after the end of treatment. Patient comfort was measured using a Visual Analog Scale (VAS) at the end of each treatment. Data were analyzed by analysis of variance.Result There was a statistically significant difference in the comfort of the procedures, with G2 and G3 being better than G1. Additionally, an increase in the diastolic blood pressure was observed in sodium bicarbonate jet group evaluated just after the procedure.Conclusion The conventional prophylaxis is more comfortable from the patient stand point and does not alter arterial pressure.

ResumoIntrodução A quantidade de pacientes hipertensivos está aumentando e, a profilaxia com jato de bicarbonato de sódio é bastante empregada na prática clínica usando grande quantidade dessa substância em um período curto de tempo que poderia aumentar a pressão arterial.Objetivo Foi avaliado a alteração da pressão arterial antes e após os dois métodos de profilaxia dental e obtido a opinião de conforto do paciente em relação a esses métodos.Material e método Selecionou-se 20 pacientes, na faixa etária de 18 a 30 anos, que necessitavam de profilaxia para remoção de biofilme dental e foram submetidos aos três tipos diferentes de tratamento: jato de bicarbonato de sódio (G1), profilaxia convencional (G2), e controle (G3), em intervalos de um mês entre eles. Os pacientes foram divididos de forma randomizada. As aferições realizaram-se antes da profilaxia, imediatamente ao fim do procedimento, 15 e 30 minutos após o término do tratamento. O conforto do paciente foi medido por meio de uma Escala Analógica Visual (VAS) após o final de cada tratamento. Os dados foram analisados por meio de teste de Variância.Resultado Houve diferença estatisticamente significante quanto ao conforto dos procedimentos, sendo G2 e G3 melhores que G1. Observou-se aumento da pressão arterial diastólica no grupo jato de bicarbonato de sódio imediatamente após a profilaxia.Conclusão A profilaxia convencional é mais confortável do ponto de vista do paciente e não altera a pressão arterial.
Comparação entre dois métodos de profilaxia dental: avaliação da pressão arterial e conforto do paciente. Estudo clínico controlado e randomizado
Keywords: Dental prophylaxis; bicarbonate sodium; arterial pressure; clinical trial; Profilaxia dentária; bicarbonato de sódio; pressão arterial; ensaio clínico